Teacher in the Loop AI (TiL-AI): A Strategy for Empowering Educators in Developing Countries through OER Adaptation - Venkataraman Balaji; Betty Obura Ogange; Tony John Mays (Journal of Learning for Development)
Artificial intelligence (AI) is rapidly transforming various sectors, including education. One of the most promising applications of AI in education is in the development and adaptation of Open Educational Resources (OER). COL’s Teacher-in the-Loop (TiL-AI) initiative empowers teachers and TVET trainers across the Commonwealth to leverage generative AI (GenAI) in adapting OER to fit national and local curricula, ensuring relevance and cultural resonance. Synergising the power of GenAI with the teacher’s role, we can improve the quality of AI-generated content and empower teachers with a deeper understanding of both AI and OER and their combined potential in education. This paper is based on Phase 1 of the project.